A non-symmetric sulfur-based O, C, O-chelating pincer ligand leading to chiral germylene and stannylene. Issue 7 (28th January 2019) - Deak, Noemi; Thillaye du Boullay, Olivier; Moraru, Ionut-Tudor; Mallet-Ladeira, Sonia; Madec, David; Nemes, Gabriela
Abstract : New chiral heteroleptic germanium(ii ) and tin(ii ) metallylenes were obtained using 1-( para -tolylsulfinyl)-3-tosyl-5- tert -butyl-benzene as a non-symmetric O, C, O -chelating pincer ligand. Abstract : New chiral heteroleptic germanium(ii ) and tin(ii ) metallylenes were obtained using 1-( para -tolylsulfinyl)-3-tosyl-5- tert -butyl-benzene as a non-symmetric O, C, O -chelating pincer ligand. Crystallographic analysis and DFT calculations indicate that the non-symmetric sulfinyl–sulfonyl pincer ligand acts as an O, C, O -coordinating pincer-type-ligand with predominant sulfinyl intramolecular SO coordination to germanium(ii ) and tin(ii ) centers.